Entre mulheres e a água : riscos neoplásicos na população feminina por veiculação hídrica em Paripiranga/BA - Fraga, Francielly Vieira (2019)
Water resources contamination and its relationship with environmental health are bruising discussions in the contemporary context. Thus, associating this theme with the use of pesticides in the field and the increase in cancer rates in the population, there is an interdisciplinary problem of relevant discussion. Regarding to the problem, it is aggravated when women are typified as risky subjects in this context, still far from the rural and agricultural contexts, while exposed to contamination and neoplasms. Therefore, this thesis has as main objective aims to analyze the relationship between water resources contamination in Paripiranga (BA) and its influence on neoplastic risks in the female population. For this, active teaching-learning methodologies were used, as learning techniques based on PBL and problematization, through the Maguerez Arch, as innovative strategies, used in all their stages, differentiated and united from the propositions of applications in the outline of the research. Thus, in order to promote the operationalization of the proposed objectives, the following procedures were built: theoretical foundation; field research with forty women, research subjects; water collection and analysis from four communities in the research territory; planning and execution of activities of extension and exchange of knowledge and experiences, besides the construction of technological educational product: Protocol and App. The approach was exploratory and descriptive and involved qualitative and quantitative data. Based on the active methodology and its aspects, the sociocultural relations of the community, the use of water, the health context and the water process contamination were analyzed, unifying the risks for cancer. In the conclusions, it was observed that the presence of contaminants in the collected water, associated with the interviews, which pointed out the use of pesticides, with risk handling, as well as the presence of signs of risk and deficiency in health monitoring, denotes the risk to which these women are exposed, especially in the neoplastic axis, responsible for the high rates of death and illness in the region. It was also noted that the use of active methodologies enabled the interaction, formation and promulgation of education with the student/community/health unit as a learning center in a single link of improvements and continuing and emancipatory education.